Canalicular domain structure and function in matrix-free hepatic spheroids. (22nd November 2019) - Sharma, Vikas Raj; Shrivastava, Ananya; Gallet, Benoit; Karepina, Elizaveta; Charbonnier, Peggy; Chevallet, Mireille; Jouneau, Pierre-Henri; Deniaud, Aurélien
Abstract : The combined use of light sheet fluorescence microscopy and 3D electron microscopy enables to reveal the fine details of bile canaliculi structure and function in matrix-free hepatic spheroids. Abstract : Liver is pivotal in organism metabolism. This organ is receiving nutriments from the portal vein and then storing, metabolizing, distributing in the circulation or excreting excess and xenobiotics in bile. Liver architecture and hepatocyte polarization are crucial to achieve these functions. To study these mechanisms in details, relevant cell culture systems are required, which is not the case with standard 2D cell culture. Besides, primary hepatocytes rapidly de-differenciate making them inefficient in forming physiological system. Herein, we used an hepatoma-derived cell line to produce matrix-free hepatic spheroids and developed an integrated structural cell biology methodology by combining light sheet fluorescence microscopy and 3D electron microscopy to study their function and structure. Within these spheroids, hepatocytes polarize and organize to form bile canaliculi active for both organics and inorganics excretion. Besides, live imaging revealed the high dynamic of actin networks in basal membranes compared to their high stability in the apical pole that constitutes bile canaliculi. Finally, the first structure of active bile canaliculi was solved at nm resolution and showed the very high density of microvilli coming from all cells constituting the canaliculus. Therefore, this study is the first comprehensive and in-depth functional and structural study of bile canaliculi in a physiological-relevant context.